Reading the human body: physiognomics and astrology in the Dead Sea scrolls and Hellenistic-early Roman period Judaism - Popović, Mladen (Studies on the texts of the desert of Judah 0169-9962, 2007)
Offering fresh reconstructions and interpretations of physiognomic and astrological texts from Qumran in comparison with Babylonian and Greco-Roman texts, this book gives a fresh view of their sense, function, and status within the Qumran community and Second Temple Judaism